Preparation of a hydrophilic and antibacterial dual function ultrafiltration membrane with quaternized graphene oxide as a modifier - Liu, Haosong; Liu, Xuyang; Zhao, Fangbo; Liu, Yang; Liu, Lijia; Wang, Lihong; Geng, Chengbao; Huang, Pei (Journal of colloid and interface science, 2020)
[Display omitted] In order to improve the anti-biofouling performance of ultrafiltration membrane, quaternized graphene oxide (QGO) was synthesized as a membrane modifier by in-situ growth of quaternary ammonium salt on the graphene oxide surface. A hydrophilic and antibacterial dual functional membrane was prepared with this kind of modifiers by immersion phase inversion method. The modified membrane obviously exhibits enhanced hydrophilicity, antibacterial and mechanical properties than the unmodified Polyvinylidene fluoride (PVDF) membranes. At the same time, it is proved that graphene oxide, as a carrier of quaternary ammonium salt, can significantly reduce the loss of antibacterial substances from the membranes.